Universitários de educação física são otimistas e motivados durante a vida acadêmica? - Borsato Passos, Patricia Carolina (Educación Física y Ciencia.)
The objective is to analyze the life orientation and the academic motivation of university students of the Physical Education course of study during the four years of initial training. Twenty-four undergraduate students of the full-time Physical Education course from a public university in southern Brazil participated in this longitudinal study. As research instruments, the Life Orientation Test (TOV-R), the Academic Motivation Scale and an identification questionnaire were used. The Friedman test, the Mann-Whitney U test, the Kruskal-Wallis test and the Spearman correlation (p <0.05) were used for the statistical analysis. The results show that the level of optimism did not change over the years, although the levels of motivation showed significant differences among the years. The results of the correlation showed that the fewer hours of physical exercise performed by the students, the more unmotivated they were (p=0.04) and the higher the age group, the higher the levels of intrinsic motivation (r=0.60). We conclude that Physical Education students are optimistic throughout initial training. However, it was verified that during the first year of training academics are more unmotivated than during other years.